Konsep Desa Wisata: Pengembangan Potensi Desa, Pelestarian Agama, Budaya dan SDM - I Made Putra Aryana (UHN IGB Sugriwa Denpasar, 2019)
The government's strategy to overcome development inequality in urban and rural areas is to pay great attention to rural development. Villages are given autonomy to regulate and manage community interests. The effort made by the village to improve thestandard of living of its people is to form a tourism village. Through literacy and literature study, efforts can be made to develop tourism villages. Tourist Attraction Business is an effort or activity that uses something that is unique, the beauty of natureand culture that is owned by the community which is a particular target for tourist visits. Every village has the potential to become a leading tourism commodity. The Regional Government of Bali has determined that tourism developed in the area of Bali isCultural Tourism. Cultural tourism is a type of tourism that develops and develops using Balinese culture inspired by Hinduism. As much as anything and as good as the potential that will become a superior commodity if tourism business actors (villages)are not ready with the science of tourism management, then we can be sure that tourism activities will not last long.